The Relationship between Organizational Commitment and Organizational Cynicism Levels of Accounting Employees in Hotel Enterprises: The Case of Kemer (Global Journal of Management and Business Research, 2020)
The purpose of this research; to determine the organizational commitment and organizational cynicism levels of the accounting employees in hotel businesses. It is also determined whether demographic factors make a differencelin the level of organizational dependency and cynicism of employees. For this purpose, a survey study was conducted between 150 and August 2019 on 150 personnel working in hotel businesses operating in Kemer district of Antalya province. Data obtained by random sampling method were analyzed in SPSS 20 package program. As a result of the research, it has been determined that the demographic characteristics of the employees are effective on organizational commitment and organizational cynicism, and also there is a relationship between the organizational commitment levels and the organizational cynicism levels of the accounting employees in the hotel enterprises.
Keywords: organizational cynicism; organizational commitment; accounting employees; hotel enterprises; organizational behavior